A New Approach for Evaluating Palatine Tonsillar Hypertrophy in Children Based on Ultrasound: A Pilot Study. (7th June 2022) - Geng, Chenchen; Tian, Shuxu; Song, Qian; Yang, Liu; Li, Ye; Wang, Huihui; Tian, Xueping; Ge, Ling
Abstract : Objectives: To develop a novel ultrasound (US) plane to diagnose palatine tonsillar hypertrophy objectively in children. Methods: Tonsillar ultrasonography of children (age 2–14 years) who had a clinical diagnosis of tonsillar hypertrophy or not were analyzed retrospectively. Clinical data (including gender, age, body mass index (BMI)), and volume ( V ) of tonsils measured by the US, were recorded. Furthermore, we found a new US plane to diagnose tonsillar hypertrophy and named it the submental oblique cross‐section. In this plane, diameters of the left tonsil, right tonsil, and central oropharynx were designated as T 1, T 2, and O . Then, we calculated the ratio by the formula ( T 1 + T 2)/ O . Results: A total of 172 cases (85 hypertrophy and 87 non‐hypertrophy) were included in this study. There were no significant differences in gender ( P = .844), age ( P = .666), and BMI ( P = .089) between the groups. In the non‐hypertrophy group, the V of both sides had a positive linear correlation with age or BMI. In contrast, there was no linear correlation between ratio and age or BMI. The area under the curve (AUC) of ratio and V was 0.970 (95%CI: 0.947–0.993) and 0.835 (95%CI: 0.778–0.893) by receiver operating characteristic (ROC) analysis, respectively. The optimal cutoff value of ratio for diagnosis of tonsillar hypertrophy was 2.293 (sensitivity = 88.2%, specificity = 95.4%). Conclusions: We established a new US section to evaluate tonsillar hypertrophy. This approach could be easily acquired and provide a reference value to guide clinical practice.